Development of Nutrition Literacy Scale for Middle School Students in Chongqing, China: A Cross-Sectional Study - Wang, Tiankun; Zeng, Mao; Xie, Changxiao; Zhu, Yuzhao; Shi, Zumin; Sharma, Manoj; Zhao, Yong (Frontiers in Nutrition, 2022)
Background Information on nutrition literacy of middle schoolers is limited and tools for measuring nutrition literacy of middle schoolers are inadequate. Nutrition literacy has a positive effect on health. Improving children's nutrition literacy can help them to master the necessary nutritional knowledge, develop a healthy lifestyle, and learn to supplement nutrition according to their own needs for healthy growth. Objectives To develop the Chongqing Middle school student Nutrition Literacy Scale (CM-NLS). Methods Three experiments were conducted. A theoretical framework and an initial item pool of CM-NLS were established based on the literature review. And the two-round Delphi method was used to explore the suitable acceptance indicators and items. Item evaluation and reduction were performed using the classical test theory. Then, the items in the final CM-NLS were tested for their validity and reliability amongst 462 middle school students. The construct validity was assessed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The internal consistency reliability and split-half reliability were evaluated using Cronbach's alpha coefficients. Results The final CM-NLS consisting of 52 items that were based on three primary items (functional, interactive and critical) and six sub-items (obtain, understand, apply, interact, medial literacy and critical skill) was developed and validated. EFA suggested six factors explaining 69.44% of the total variance (Kaiser–Meyer–Olkin test = 0.916, Bartlett's test χ2 = 5,854.037, P < 0.001). CFA showed that the model fit the data adequately, with χ2/df = 1.911, root mean square error of approximation = 0.063, goodness-of-fit index = 0.822 and adjusted goodness of fit index = 0.790. The total CM-NLS Cronbach's alpha values of internal consistency and split-half reliability were 0.849 and 0.521, respectively, with reasonable reliability. Conclusions CM-NLS is a valid and reliable instrument for assessing nutrition literacy among middle school students in Chongqing. Specifically, it could be used by practitioners for needs assessment before the implementation of a nutrition education program.